Kontroversi Surat Al-Fatihah Dalam Pandangan Arthur Jeffery - Dhulkifli, Muhammad Luthfi (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2019)
AbstractAmongst some orientalist of Qur’anic studies, Arthur Jeffery was one of the controversial figures for the idea of a critical edition of the Qur’an. For Jeffery, the Qur’an existed today is unreasonable and its arrangement is clearly haphazard. One of his critical argument is surah al-Fatihah which indicated not originally part of the Qur’an. His work “the variant readings of the Fatihah” showed some peculiar nature of al-Fatiha with the evidence of two Fatihah different versions. Jeffery’s variants study is a polemical argument as its contradicts to the Muslim scholar arguments. For Muslim scholars, al-Fatihah is an integrated part of Qur’an. Therefore, this article will analyze Jeffery’s argument on al-Fatihah through a descriptive-analytic method. Based on historical, language, and qira’ah study, Jeffery’s argument is incorrect. In addition, Jeffery failed to show the existence of his evidence of variant of al-Fatihah.Keywords: Critic; Controversy; Fatiha; Muslim; the Qur’an AbstrakDiantara sekian banyak para orientalis pengkaji al-Qur’an, Arthur Jeffery merupakan salah satu sosok yang paling kontroversial dengan gagasannya untuk membuat al-Qur’an edisi kritis. Menurut Jeffery, al-Qur’an yang ada saat ini sangat tidak jelas dan susunannya dilakukan secara sembarangan. Salah satu bagian yang Jeffery kritisi adalah surat al-Fatihah yang dianggap bukan bagian dari al-Qur’an. Dalam tulisannya yang berjudul the variant readings of the Fatihah, dia menunjukkan kejanggalan dalam surat al-Fatihah dengan menunjukkan bukti dua variasi surat al-Fatihah yang berbeda. Kajian ini mengundang polemik karena bertentangan dengan pandangan para sarjana Muslim yang menganggap al-Fatihah sebagai bagian penting dari al-Qur’an. Tulisan ini akan menganalisasi pandangan Jeffery terhadap surat al-Fatihah melalui metode deskriptif-analitis. Melalui kajian historis, kebahasaan, dan ilmu qira’at, argumen skeptis Jeffery terhadap al-Fatihah terbantahkan. Ditambah lagi, Jeffery tidak mampu membuktikan keberadaan variasi surat al-Fatihah yang dia yakini. Kata Kunci: al-Fatihah; al-Qur’an; Kontroversi; Kritik; Muslim